Low contraceptive utilization among young married women is associated with perceived social norms and belief in contraceptive myths in rural Ethiopia - Dingeta, Tariku (PLoS One, 2021)
INTRODUCTION: Despite the increasingly wider availability of contraceptives and the high levels of unmet need for family planning in rural Ethiopia, contraceptive utilization among young married women is low. Studies on associated factors in Ethiopia so far have been focused on individual factors with little emphasis on socio-cultural factors. This study aimed to assess the association between contraceptive utilization and socio-cultural factors among young married women in Eastern Ethiopia. METHODS: A community-based survey was conducted among young married women aged 14–24 years. A total of 3039 women were interviewed by trained data collectors using a structured questionnaire. Adjusted Odds Ratio (AOR) with 95% Confidence Intervals (CI) was used to identify factors associated with contraceptive utilization using multivariable logistic regression analysis. RESULTS: The current contraceptive prevalence rate was 14.1% (95% CI: 12.8–15.5). Perceived social approval (AOR = 1.90; 95% CI = 1.60–2.30) and perception of friends’ contraceptive practice (AOR = 1.34; 95% CI: 1.20–1.54) were significantly and positively associated with contraceptive utilization. On the contrary, increased score of belief in contraceptive myths was significantly and negatively associated with contraceptive use (AOR = 0.60; 95% CI: 0.49–0.73). Moreover, recent exposure to family planning information (AOR = 1.67; 95% CI: 1.22–2.28), ever-mother (AOR = 9.68; 95% CI: 4.47–20.90), and secondary and above education level (AOR = 1.90; 95% CI: 1.38–2.70) were significantly associated with higher odds of contraceptive utilization. CONCLUSION: Only about one-in-seven young married women were using contraceptive methods. Socio-cultural factors significantly influence young married women’s contraceptive utilization. Interventions to address social norms and pervasive myths and misconceptions could increase the use of contraceptive methods in young married women.